TASS upolnomochen zaiavit' 1-2 . TASS Is Authorized to Declare…part 1, 2 - Fokin, Vladimir (Gosteleradio SSSR, 1984)
A spy is sent to Moscow. Soviet intelligence is trying to neutralize him and thus prevent a revolt, prepared by the CIA, in the fictional third-world state of Nagonia.